Effects of a Haptic Augmented Simulation on K-12 Students' Achievement and their Attitudes towards Physics - Civelek, Turhan; Ucar, Erdem; Ustunel, Hakan; Aydin, Mehmet Kemal (MODESTUM LTD, 2014)
The current research aims to explore the effects of a haptic augmented simulation on students. achievement and their attitudes towards Physics in an immersive virtual reality environment (VRE). A quasi-experimental post-test design was employed utilizing experiment and control groups. The participants were 215 students from a K-12 school in Istanbul, Turkey. The students were split into two groups and each group were respectively taught the subject, mass gravity in the solar system., employing traditional instructional methods for the control group and, as a treatment, utilizing a haptic force feedback application in a VRE for the experiment group. The data was gathered through an attitude questionnaire and an achievement test was analyzed administering descriptive and comparative analyses. Findings illustrated that use of a haptic force feedback application in a VRE had a significant and positive effect on students. achievement, as well as on their motivation, encouragement, autonomy, and learning quality.
Keywords: Haptics force feedback applications; immersive virtual reality environments; haptics augmented simulations; experiential learning; Education & Educational Research